Assessment of the environmental sustainability of restaurants in the U.S.: The effects of restaurant characteristics on environmental sustainability performance. Issue 2 (3rd March 2020) - Jang, Yoon Jung; Zheng, Tianshu
ABSTRACT: This paper investigated the current levels of environmental sustainability in restaurants across the U.S. to determine whether a restaurant's proclivity for environmental sustainability depended on its characteristics such as chain affiliation or restaurant type. A web-based survey was administered to 2, 500 top-level restaurant managers, from which a total of 218 responses were judged as usable. The data were analyzed using independent sample t-tests and ANOVA. This study presents an in-depth account of the environmental sustainability in restaurants across the U.S. based on an evaluation of top-level managers. This study also highlights the differences in restaurant environmental sustainability across different restaurant segments.